PREDIKSI EROSI PADA BEBERAPA PENGGUNAAN LAHAN DI DTA DANAU LINDU SUB DAS PALU PROVINSI SULAWESI TENGAH - Ikra, Ikra; Ramlan, Ramlan; Isrun, Isrun (AGROTEKBIS, 2018)
The research was conducted in Lake Lindu Watershed Sub DAS Palu of Lindu Subdistrict of Sigi Regency and soil analysis was carried out in Soil Science Laboratory Laboratory of Tadulako University. The purpose of this study is to predict the rate of soil erosion and determine the index of erosion hazard in some land use in Lake Lindu watershed area Palu Sub-waters of Central Sulawesi Province. The benefits of this research are as a source of information for the government in general and provide information on the size of the erosion hazard index on some agricultural and non-agricultural land use so that it can be used sustainably. This research method was done by using survey method, soil sampling, soil anilisis, type and source of data and collect data through observation and interview. Data processing to obtain the result of erosion prediction is processed by using USLE equation (Universal Soil Loss Equation) by entering primary data and secondary data into USLE equation that is long and slope factor, Plant Management Factor and Soil Conservation Factor (CP), tolerated Erosion (TSL), and the Erosion Hazard Index (EHI). Based on the research conducted in Lake Palu Lake Basing Sub Palu about the prediction of erosion on some land use it was found that the erosion hazard that occurs in some units of land in Lake Lindu watershed Palu sub watershed included in the criteria of high, medium to low. The average value of erosion thatwas tolerated 17.07 ton-1year-1. The rate of erosion in Lake Lindu Watershed Palu is dominant due to soil erodibility, crop management and conservation measures. Conservation actions that need to be done are to maintain the existing vegetation, the use of plant remains as mulch, the use of bench terraces, guludan, reforestation and land evaluation.